2020
DOI: 10.1155/2020/1627824
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus and Epstein-Barr Infections: Prevalence and Impact on Patients with Hematological Diseases

Abstract: Cytomegalovirus (CMV) and Epstein-Barr virus (EBV) infections are widely distributed throughout the world. EBV is linked to various hematological and autoimmune disorders whereas CMV might play important role in the progression of chronic hematological diseases, such as hemoglobinopathies, lymphomas, myelomas, hemophilia, and aplastic and sickle cell anemia. Both viruses produce a viral homolog of human interleukin-10 that can cause general suppression of immune response, increasing susceptibility to other inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 106 publications
0
23
1
Order By: Relevance
“…EBV and CMV infections have been associated with several hematological diseases, especially regarding the progression of hemoglobinopathies, lymphomas, myelomas, hemophilia, sickle cell and aplastic anemia diseases [22]. In this study, patients carriers of ITP showed the highest prevalence rates for EBV infection and EBV/CMV coinfection.…”
Section: Discussionmentioning
confidence: 60%
“…EBV and CMV infections have been associated with several hematological diseases, especially regarding the progression of hemoglobinopathies, lymphomas, myelomas, hemophilia, sickle cell and aplastic anemia diseases [22]. In this study, patients carriers of ITP showed the highest prevalence rates for EBV infection and EBV/CMV coinfection.…”
Section: Discussionmentioning
confidence: 60%
“…Although the association of EBV with several types of cancer is well documented, this association has not been documented for CMV and only a few studies reported that CMV might be associated with some cancers in humans. In this regard, Silva et al reported that CMV might be associated with hematologic malignancies including myeloid tumors (37). Moreover, CMV has been considered as a potential causative factor in the development of colon cancer (38).…”
Section: Discussionmentioning
confidence: 99%
“…Herpesvirus reactivations are frequent after solid organ or allogeneic stem cell transplants. CMV reactivation occurs in 12–67% of patients undergoing autologous stem cell transplant and 2–39% oncohematologic non-transplant subjects [ 78 ]. A clear association with alemtuzumab emerged from prospective studies [ 79 ].…”
Section: Viral and Mycobacterial Reactivations During Aiha Treatmementioning
confidence: 99%